Osteogenesis activity of fractions extracted from Clinacanthus nutans (Burm. F.) Lindau - Phuong, Pham Thi Thu; Minh, Nguyen Thi Hong; Lien, Quach Thi; Huong, Nguyen Thi Thanh; Phuong, Nguyen Thi Mai (Academia Journal of Biology, 2020)
Osteogenesis activity of fractions extracted from Clinacanthus nutans was evaluated on an in vitro model using osteoblast MC3T3-E1 cells. The results showed that all fractions, including ethanol (EtOH), n-hexane, ethyl acetate (EtOAc) and butanol (BuOH) were not significantly toxic to the osteoblast cells at the test concentrations of 5, 10, 25, and 50 µg/mL. The EtOH and EtOAc fractions exhibited the highest osteogenesis activity in terms of enhancement of alkaline phosphatase (ALP) and mineralization activity of MC3T3-E1 cells, especially the EtOAc fraction which increased ALP activity up to > 30% and mineralization activity up to > 100%. Thus, the EtOAc fraction shows osteogenesis activity through stimulating activites of the two markers for bone generation including ALP and mineralization in osteoblast cells. The fraction is now under extensive investigation to isolate and fully understand the modes of action of the active compounds.